2021
DOI: 10.1016/j.molp.2021.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Loss of two families of SPX domain-containing proteins required for vacuolar polyphosphate accumulation coincides with the transition to phosphate storage in green plants

Abstract: Phosphorus is an essential nutrient for plants. It is stored as inorganic phosphate (Pi) in the vacuoles of land plants but as inorganic polyphosphate (polyP) in chlorophyte algae. Although it is recognized that the SPX-Major Facilitator Superfamily (MFS) and VPE proteins are responsible for Pi influx and efflux, respectively, across the tonoplast in land plants, the mechanisms that underlie polyP homeostasis and the transition of phosphorus storage forms during the evolution of green plants remain unclear. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 35 publications
2
35
0
Order By: Relevance
“…The outgroup genes used in this study were grouped in box E clustered with EXS clade. Overall, topology of EXS class is consistent with He et al, (2013), in that basal plants (lycophytes and moss) EXS homologs were grouped separately from the angiosperms, and also with the previous reports on EXS genes that monocots only possess homologs for AtPHO1 and AtPHO1;H1 [6, 24, 35].…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The outgroup genes used in this study were grouped in box E clustered with EXS clade. Overall, topology of EXS class is consistent with He et al, (2013), in that basal plants (lycophytes and moss) EXS homologs were grouped separately from the angiosperms, and also with the previous reports on EXS genes that monocots only possess homologs for AtPHO1 and AtPHO1;H1 [6, 24, 35].…”
Section: Resultssupporting
confidence: 89%
“…Although Wang et al [24] reported one SPX-MFS in M. polymorpha genome, we could not find an intact SPX-MFS domain, but SPX-Sugar_tr domain with a highly similar motif composition with other MFSs was identified (Additional file 1: Figure S3). As it has previously been reported, PHT5 genes in B. napus have SPX domain connected to overlapping MFS and Sugar_tr domains [36], however, we only found SPX and Sugar-tr domains in M. polymorpha genome.…”
Section: Protein Motifs Gain and Loss In Spx Family Throughout Evolutionmentioning
confidence: 74%
See 2 more Smart Citations
“…However, when and how this transition occurs during plant evolution remained unclear until recently. Wang et al (2021) showed that the transition of vacuolar P storage form from polyP to Pi occurred in the ancestor of later diverging streptophytes It was also suggested that this transition is a consequence of the loss of two gene families (SPX-SLC and SPX-VTC) involved in polyP homeostasis (Wang et al, 2021). Given that vacuolar polyP has not been documented in land plants, the transition of vacuolar P storage form from polyP to Pi is a vital node during plant evolution.…”
Section: Pi Absorption and Vacuolar P Storage In Unicellular Green Algae And Multicellular Land Plantsmentioning
confidence: 99%